1979
DOI: 10.1007/bf00401013
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of telangiectatic osteosarcoma

Abstract: Recent investigations have shown that telangiectatic osteosarcoma has a poorer prognosis than other osteosarcomas. To elucidate the histogenesis of TOS two cases were investigated on the electron microscopic level. The results show that besides anaplastic, osteoblast-like, and fibroblast-like tumor cells angiosarcomatous components can be observed in this malignant bone tumor, which are characterized by endothelial cells with pinocytotic vesicles, tight intercellular junctions, fine fibrils, and so-called Weib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Weibel-Palade bodies, pinocytic vesicles, and tight intercellular junctions are identified within the cell cytoplasm; these features further suggest this tumor derives from multipotential stem cells of mesenchymal origin. 7,8 …”
mentioning
confidence: 99%
“…Weibel-Palade bodies, pinocytic vesicles, and tight intercellular junctions are identified within the cell cytoplasm; these features further suggest this tumor derives from multipotential stem cells of mesenchymal origin. 7,8 …”
mentioning
confidence: 99%
“…Endothelial cell‐like structures, including pinocytic vesicles, tight intercellular junctions and Weibel–Palade bodies, are seen in the cytoplasm of these cells. Such observations suggest that this type of malignant bone tumour may be derived from multipotential stem cells of mesenchymal origin, with possible differentiation along various pathways . These ultrastructural observations could further explain the minimal SATB2 immunoreactivity in this rare subtype of osteosarcoma.…”
mentioning
confidence: 76%
“…TOS is a high-grade type of OS arising at the metaphyseal level of long bones, in particular, in the proximal tibia and distant femur [23]. This intraosseous tumor presents several characteristic histologic aspects, such as the presence of several cavities filled with clotted blood and segmented by several septa, in which it is possible find several types of tumor cells (i.e., endothelial, fibroblast and osteoblast-like cells), which, in addition to characteristic radiographical and prognostic aspects, show that TOS is a specific and quite different type of OS [24].…”
Section: Discussionmentioning
confidence: 99%
“…Later, ultrastructure analysis of TOS samples using electron microscopy showed that the cystic cavities are filled with clotted blood and segmented by several septa, which often contain tumor cells. Malignant cells (anaplastic, osteoblastand fibroblast-like tumor cells) can produce the osteoid matrix, which appears as a lacelike material between the observed septa and the tumor cells [24]. Electron microscopy has also shown that certain areas of TOS present the typical pattern of OS lesions, where osteoblast-like tumor cells are embedded in a large amount of osteoid matrix [24].…”
Section: Introductionmentioning
confidence: 99%